Effect of Balanite aegyptiaca Seeds Oil on Some Haematological and Serum Biochemical Parameters in Broiler Chickens (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
This research was conducted to find out what role of Balanite aegyptiaca seeds oil on haematological and biochemical parameters using broiler chickens. Preliminary qualitative phytochemicals tests were carried out on the B. aegyptica seeds oil in accordance with accepted practices for detecting secondary metabolites. Forty chicks were employed in the study, and they were split into four different groups, each group containing 10 chicks and brood on normal diet for two weeks, after which each group were administered varying concentration of B. aegyptiaca seeds oil (1ml, 1.5ml and 2ml), while in the Control group no oil was administered. Blood samples were collected and tested at the University of Maiduguri Veterinary College laboratory for haematological (PCV, HB, RBC and WBC) and biochemical parameters (AST, ALT, ALP, ALB and TP) were evaluated two weeks after treatment. The result of phytochemical analysis of B. aegyptica seeds oil reveals the presence of alkaloids, steroids, flavonoids, saponins and cardiac glycosides while tannins terpenoids, sterols, anthraquinones were not detected. The result of haematological parameters showed a significant increase in the levels of RBC, PCV, HB as well as WBC of the test samples when compared with the control group. This indicates that the administration of B.aegyptiatica seeds oil significantly (p0.05) between the treated and untreated groups.